Enhanced energy storage properties of BiAlO3 modified Bi0.5Na0.5TiO3–Bi0.5K0.5TiO3 lead-free antiferroelectric ceramics. Issue 10 (July 2017) - Yu, Zhenglei; Liu, Yunfei; Shen, Muyi; Qian, Hao; Li, Fangfang; Lyu, Yinong
Abstract: Lead-free (1− x )(0.75Bi0.5 Na0.5 TiO3 –0.25Bi0.5 K0.5 TiO3 )– x BiAlO3 (BNT–BKT–100 x BA, x =0–0.10) ceramics were prepared by two-step sintering method and their phase structure, micro morphology and electrical properties were systematically investigated. X-ray diffraction analysis indicates a pure perovskite phase for x ≤0.06 as well as a structural evolution from a tetragonal toward a pseudocubic phase. Transmission electron microscopy study of the x =0.04 composition reveals the existence of antiferroelectric phase with a 0 a 0 c + oxygen octahedron tilting which is in the form of nano-domains. Polarization-electric field and current-electric field hysteresis loops demonstrate that the increase of BA concentration destroys the ferroelectric order and strengthens antiferroelectric order. A much enhanced energy storage density of 1.15 J/cm 3 and efficiency of 73.2% is achieved under 105 kV/cm at x =0.06. In addition, its energy storage property is found to depend weakly on temperature within the measurement range of 25–150 °C.